2009
DOI: 10.1075/arcl.7.09gul
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing verb meaning in a second language

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 41 publications
4
43
3
3
Order By: Relevance
“…In the field of cross-linguistic influence in language learning (discussed in e.g., Gullberg, 2009), it is assumed that most L2 difficulties arise when an existing L1 category has to be split up into two L2 categories, because it ''involves the need to shift semantic boundaries of existing categories in the L1 and re-structure semantic-conceptual representations" (Gullberg, 2009, p. 223). L2 production studies on placement events show that fully mastering two specific semantic categories of placement in an L2 is indeed highly challenging (e.g., Alferink & Gullberg, 2014;Berthele, 2012;Gullberg, 2009). Perhaps such conceptual-semantic representations will never be strong enough for predictive use in L2 processing, unlike morphosyntactic representations (such as gender; cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of cross-linguistic influence in language learning (discussed in e.g., Gullberg, 2009), it is assumed that most L2 difficulties arise when an existing L1 category has to be split up into two L2 categories, because it ''involves the need to shift semantic boundaries of existing categories in the L1 and re-structure semantic-conceptual representations" (Gullberg, 2009, p. 223). L2 production studies on placement events show that fully mastering two specific semantic categories of placement in an L2 is indeed highly challenging (e.g., Alferink & Gullberg, 2014;Berthele, 2012;Gullberg, 2009). Perhaps such conceptual-semantic representations will never be strong enough for predictive use in L2 processing, unlike morphosyntactic representations (such as gender; cf.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly found pattern in the acquisition of this distinction is overextension: Narasimhan and Gullberg (2011) for example report an overextension of the verb leggen by 4-and 5-year old children acquiring Dutch. In L2 production, Gullberg (2009) found that English L2 users of Dutch overgeneralize the verb zetten, as well as general action verbs like doen 'to do' when describing placement events; Berthele (2012) reports an overuse of the verb legen and the general action verb tun 'to do' in Romansh L2 users of German. Alferink and Gullberg (2014), investigating early French-Dutch bilinguals, report an overgeneralization of leggen in Dutch.…”
Section: Placement Eventsmentioning
confidence: 99%
“…Less research has been done about placement verbs, except for some languages as Dutch (Gullberg 2009;Lemmens 2002 and, Danish (Hijazo-Gascón, Cadierno & Ibarretxe-Antuñano 2016), or Swedish (Viberg 1998). For a cross-linguistic perspective, Kopecka & Narasimhan (2012) is also worth mentioning.…”
Section: ) Wo Hast Du Die Zeitung Hingetan?mentioning
confidence: 99%
“…Adopting a crosslinguistic perspective, Section 4 zooms in on some of the difficulties possibly encountered by speakers of Romance languages when learning German. Because of the "asymmetry in the encoding of placement" (Narasimhan et al 2012: 3) between Germanic and Romance languages, learners of satellite-framed languages have to expand semantic categories acquired in their mother tongue to fit the categories of the L2 (Gullberg 2009;Ijaz 1986). But often, a simplification through the non-use of placement (and posture) verbs is taking place (Gullberg 2009: 8).…”
Section: Offers a Contrastive Analysis Of Placement Verbs In German Andmentioning
confidence: 99%
See 1 more Smart Citation